Akesibilitas dan Kesadaran Kebangsaan: Sebuah Refleksi Sejarah untuk WTBOS di Padang Panjang - Sufyan, Fikrul Hanif (Puitika, 2024)
During the late 19th and early 20th centuries, the face of Padang Panjang has changed. Initially, Padang Panjang was the only link between the Minangkabau hinterland and the west coast of Sumatra, since the discovery of black gold on the banks of Batang Lunto, changed the condition of Padang Panjang. This research is applied to the historical method, which consists of heuristics, criticism, interpretation, and historiography. Since the end of the 19th century - with the operation of the railway line - the Padang Panjang Onderafdeling has been the entry point for modernization, and ideology - from the west coast of Sumatra to the interior of Minangkabau. The impact of this is truly amazing. The existence of the railway has spurred the growth of private schools, ranging from Sumatra Thawalib, Dinijahschool, Rakjatschool, and Tablighschool. And, from the partisan schools carried the color of ideology, movement organizations, and the press that encouraged the growth of national awareness.